Evaluating Busuu.com application for speaking skills through Technology Acceptance Model (TAM): EFL Student's Perception - Fitra Roja Aufa, Aidil; khoiriyah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
English proficiency is essential in a globalized world, particularly in academic and professional settings. This study examines students' perceptions of using Busuu, an online language learning application, to enhance their speaking skills. It also looked at students' views on their experience of the platform, including its advantages and disadvantages. The research employs a mixed-methods approach, among sixty-eight speaking class students at the University of Muhammadiyah Malang. Data were collected through a Technology Acceptance Model (TAM) questionnaire and in-depth interviews. Quantitative data were analyzed using descriptive statistics, while qualitative data were subjected to thematic analysis. The findings reveal that students generally perceive Busuu as a useful and user-friendly tool for improving speaking skills, pronunciation, and independent learning. The application's structured exercises, real-time feedback, and accessibility contributed to its positive reception. However, challenges such as technical issues, limited free features, and content limitations were identified as barriers to effective utilization. Future research should explore the long-term impact of Busuu on speaking proficiency, investigate ways to integrate it with classroom instruction, and address identified limitations to maximize its effectiveness in diverse educational settings. The study contributes to the broader discourse on digital learning by reinforcing the role of scaffolding and interactionist theories in second language acquisition.